How Colleges and Universities Are Driving to Digital Transformation Today: Conceptual Model of Digital University (Designed for the University of Georgia) - Anvari, Roya; Vilmante, Kumpikaite-Valiuniene; Janjaria, Mariam (IEEE European Technology and Engineering Management Summit (Online), 2023)
This paper attempted to present the concept of university digital transformation which aims to provide a conceptual model of a digital university and propose a framework in dimensions of digital transformation at The University of Georgia. It identifies the main opportunities and strategic documents of the university in line with its vision, goals, and strategies. We refer to digital concepts and offer insight for university staff and students and contribute to possible future organizational directions to achieving sustainable development. In this article, the key features of the digital university have been studied. It reviews the conceptual framework of digital transformation and tries to understand how universities learn from direct experience, learning technology-driven and innovation organizations, encouraging and creating a healthy and sustainable ecosystem, and how universities develop conceptual frameworks for interpreting that experience.